The effect of spiritual emotional freedom technique impact to pain in cervical cancer post-chemoradiation: a review article - Hamidah Hamidah; Syahrul Rauf; Sharvianty Arifuddin; Andi Muhammad Takdir Musba; Prihantono Prihantono; Nugraha Utama Pelupessy; Irfan Idris; Agussalim Bukhari; Andriani Qanitha; Fatimah Fatimah; Elli Hidayati; Tria Astika Endah Permatasari (Healthcare in Low-resource Settings, 2024)
Chronic pain that is subjective is experienced by patients with advanced cervical cancer. Simple movements are used in spiritual emotional freedom technique (SEFT) therapy, a therapeutic approach that improves performance and achievement, addresses psychological and physical pain issues, and promotes happiness and serenity in life. In this systematic review study, we evaluate how SEFT affects patients with cervical cancer who have had chemotherapy and radiation treatment. Using databases from 2003 to 2023, including Google Scholar, PubMed, ScienceDirect, PsycINFO, and Ovid, this study employs a systematic review methodology. The keywords “spiritual emotional freedom technique (SEFT)”, “emotional freedom technique (EFT)”, and “cervical cancer” form the basis of the search strategy. Experiments and observational studies with a minimum sample size of two participants involving patients with cervical cancer meet the inclusion criteria. The results show that among patients with post-chemoradiation cervical cancer, SEFT therapy is beneficial in lowering pain, stress, and depression. Cancer patients who experience pain may see a reduction in their quality of life as well as physical health issues. Cervical cancer patients can experience marked improvements in their pain, stress, and depression when the SEFT therapy theory is applied.